PHOTOGRAPHIC ASSESSMENT OF SMILES: PRE AND POST-ORTHODONTIC TREATMENT - Noviaranny Iy; Ramlan H; Mat Saad J (Fakultas Kedokteran Gigi Unjani, 2021)
This study aims for the smile assessment and comparison between pre and post- orthodontic treatment to induce patients' interest and awareness towards orthodontic treatment. Orthodontists are in benefit from improving the treatment plan. Methods research were photographs of 59 subjects taken from postgraduate students in an orthodontic clinic using a standardised technique. Patients' smile will be evaluated, including the smile line, midline of the dental arch and relationship of the smile arch to the lower lip curvature, by observing the patients' frontal smile photographs. The smile lines are classified into four types, with type three (average smile line: gingival embrasures only visible) is the most desirable smile. The results showed that for patients' smile line, the total numb er of patients that have achieved Type 3 post orthodontic treatment is 40.4%. As for the relationship of the smile arch to the lower lip curvature, 96.6% of the patients had their maxillary incisor edges in light contact or slightly apart from the lower lip. 61% of subjects showed no deviation from the midline. Based on the survey conducted regarding patients' perception of the smile, most patients preferred the type three smile line, 86% rather than type 2 (10%), type 4 (4%), and none on type 1. Regardless of the age group and gender, type 3 is the most preferable among the participants. It can be concluded that orthodontic treatment can improve patients' appearance and impact the smile aesthetically, thus aiding orthodontists to achieve a comprehensive treatment plan to enhance the smile aesthetic, patient's compliance, and motivation towards treatment. DOI : 10.54052/jhds.v1n1.p1-10